Evaluation of Lipid Quality in Fruit: Utilizing Lipidomic Approaches for Assessing the Impact of Biotic Stress on Pecans (Carya illinoinensis) - Lingyuan Zhou; Wei Zhang; Qingyang Li; Maokai Cui; Danyu Shen; Jinping Shu; Runhong Mo; Yihua Liu (Foods, 2024)
There is a scarcity of data on how the lipid composition of oily seeds changes in response to biotic stress. Yellow peach moth (Conogethes punctiferalis) has caused massive economic losses on the pecan (Carya illinoinensis) industry. Lipidomics is used in this study to determine the lipid composition of pecan and how it changes in response to insect attack. Pecan had 167 lipids, including 34 glycerolipids (GL), 62 glycerophospholipids (GP), 17 fatty acyls (FA), 41 sphingolipids (SP), and 13 saccharolipids (SL). The effects of biotic stress on lipids, particularly GL and GP, were significant. Biotic stress significantly reduced the lipid content of chains longer than 48. Forty-four significantly different lipids were discovered as potential biomarkers for distinguishing non-infected pecans from infested pecans. In addition, we used bioinformatics to identify the five most important metabolic pathways in order to investigate the processes underlying the changes. Our discoveries may offer valuable insights for enhancing pecan production in the future and contribute novel perspectives towards enhancing the nutritional value of pecans.